Impact of priority sector lending on financial profitability: segment wise panel data analysis of Indian banks / Rajesh Desai - Desai, Rajesh (Universiti Teknologi MARA, 2021)
A sustainable and financially stable banking system is a prerequisite to achieve comprehensive growth as well as economic and social well-being of residents of any country. This research focused on analyzing profitability of Indian banks and how it is affected by lending in the priority sector. Priority sector lending (PSL) mainly includes deployment of credit to weaker and neglected segments of an economy. The study adopted a distinctive measure to represent total PSL by classifying it into four sub-segments i.e., agriculture, industrial, service, and personal credit. Applying panel least square regression with fixed and random effects model, the study concluded that agricultural lending has a significant negative impact on bank profitability whereas the service sector lending adds positive value towards financial profitability of banks. Industrial and personal credit were found to be insignificant factors affecting profitability. The study will be beneficial to banking professionals and policy makers to determine sensitive and risky sectors of lending and develop appropriate approaches to deal with them.